Adaptation of reproductive phenology to climate change with ecological feedback via dominance hierarchies. (15th November 2013) - Johansson, Jacob; Smith, Henrik G.; Jonzén, Niclas; Both, Christiaan
Summary Phenological shifts belong to the most commonly observed biological responses to recent climate change. It is, however, often unclear how these shifts are linked to demography and competitive interactions. We develop an eco‐evolutionary model to study adaptation of timing of reproduction in organisms with social dominance hierarchies. We focus on residential birds with winter flocks, where success in competition for territories among offspring depends on ranking given by prior residence. We study the effects of environmental change on breeding population densities, ensuing selection pressures and long‐term evolutionary equilibria. We consider changes in food peak date, in winter survival, in total reproductive output and in the width of the food distribution. We show that the evolutionarily stable hatching date will advance with increasing winter survival and reproductive output since these parameters increase habitat saturation and post‐fledging competition. Increasing the length of the breeding season also selects for earlier hatching date due to the reduced costs for producing offspring with high ranking. Our analysis shows that there is little correlation between short‐term and long‐term population responses across different scenarios of environmental change. However, short‐term population growth consistently predicts selection for earlier reproduction. Hence, the model identifies changed breeding population density as a key factor to understanding phenological adaptation in systems with prior residence advantages. While selection for change in reproductive phenology is often explained by changed seasonal variation in environmental variables, such as food abundance, we show that environmental change without apparent effects on seasonality can critically affect phenological adaptation. Such factors can mask or even override influences of changed seasonality on phenology. The model thus offers a conceptually new set of explanations for understanding phenological and demographic trends in a changing climate.